Non-infectious aortitis of the ascending aorta: a histological and clinical correlation of 71 cases including overlap with medial degeneration and atheroma—a challenge for the pathologist. Issue 11 (7th July 2015) - Ryan, C; Barbour, A; Burke, L; Sheppard, M N
Abstract : Aims: Aortitis is a rare but important cause of thoracic aortic disease. We describe its histopathological patterns and associations with other aortic pathologies and systemic inflammatory disease. Methods: Database searches of thoracic specimens over 17 years from two centres yielded 71 cases of non-infectious aortitis. Histological verification of tunica media inflammation was required for inclusion. Clinical information and histopathological features were recorded. Results: Three histological patterns emerged—necrotising aortitis with giant cells (53), diffuse band-like aortitis (16) and 'other' (2). 50/53 cases of necrotising aortitis with giant cells were isolated/idiopathic, while 9/16 cases of diffuse aortitis had a systemic inflammatory disease. Medial degeneration (MD) was prominent in 23/71 cases—all in the necrotising aortitis with giant cells category. Conclusions: Non-infectious aortitis is predominantly idiopathic/isolated in nature, occurring in elderly females. Two patterns emerge—(1) necrotising aortitis with giant cells, which is more likely to be idiopathic and linked to MD, suggesting a possible aetiological relationship; and (2) diffuse aortitis, which is linked to an increased risk of systemic inflammatory disease. Knowledge, therefore, of histopathological patterns may guide patient management and follow-up.